2020
DOI: 10.3390/ijgi9070425
|View full text |Cite
|
Sign up to set email alerts
|

Automated Geolocation in Urban Environments Using a Simple Camera-Equipped Unmanned Aerial Vehicle: A Rapid Mapping Surveying Alternative?

Abstract: GNSS positioning accuracy can be degraded in areas where the surrounding object geometry and morphology interacts with the GNSS signals. Specifically, urban environments pose challenges to precise GNSS positioning because of signal interference or interruptions. Also, non-GNSS surveying methods, including total stations and laser scanners, involve time consuming practices in the field and costly equipment. The present study proposes the use of an Unmanned Aerial Vehicle (UAV) for autonomous rapid mappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…During mapping, the RGB-D image frames are inserted to the HF-Net [5] neural network in order to extract keypoints and descriptors of the scene (feature extraction module), while the system based on keypoints and descriptors, predicts the camera pose, re-localizes the camera in case of a prediction failure and extracts new keyframes aiming to map the surroundings simultaneously (fig 2). Subsequently, multi-line convergence method localizes the markers in the scene using least squares optimization [4] while plane alignment defines the horizontal plane defining the pose of the origin marker [4]. Finally, all estimations are transferred from the initial SLAM based coordinate system, to the marker coordinate system which results in targets and point cloud coordinate estimations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During mapping, the RGB-D image frames are inserted to the HF-Net [5] neural network in order to extract keypoints and descriptors of the scene (feature extraction module), while the system based on keypoints and descriptors, predicts the camera pose, re-localizes the camera in case of a prediction failure and extracts new keyframes aiming to map the surroundings simultaneously (fig 2). Subsequently, multi-line convergence method localizes the markers in the scene using least squares optimization [4] while plane alignment defines the horizontal plane defining the pose of the origin marker [4]. Finally, all estimations are transferred from the initial SLAM based coordinate system, to the marker coordinate system which results in targets and point cloud coordinate estimations.…”
Section: Methodsmentioning
confidence: 99%
“…The present study, proposes a cost-effective, rapid and efficient surveying solution for GNSS-denied environments where a few minutes of walking with an RGB-D (Visual + Depth) camera on hand, are enough to map an area of interest. The proposed methodology which is based on SLAM with deep learning using the multi-line convergence (MLC) and plane alignment (PA) methods proposed in the previous stage of our work [4], is able to produce accurate coordinate estimations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Sun et al 34 developed an allin-one camera-based target detection and positioning system for fixed-wing UAVs and searchand-rescue scenarios, and they evaluated it through simulation experiments. Finally, Trigakis et al 35 demonstrated a commercial UAV that may achieve point coordinate estimation under a margin of 30 cm on a constructed point cloud. Although these research studies achieve target detection and spatial approximation in a global coordinate system, they highly depend on the used image processing approaches, the corresponding camera unit specifications and calibration procedure, and they achieve a relatively low coordinate determination accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…developed an all-in-one camera-based target detection and positioning system for fixed-wing UAVs and search-and-rescue scenarios, and they evaluated it through simulation experiments. Finally, Trigakis et al 35 . demonstrated a commercial UAV that may achieve point coordinate estimation under a margin of 30 cm on a constructed point cloud.…”
Section: Introductionmentioning
confidence: 99%